Effect of Centrifugation on Competent Cells of Escherichia coli - Zhao, Lin; Zhao, Hanxiao; Liu, Hongxing; Yang, Xianyu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
In this study, we changed centrifugation parameters (3 300 g, 2 min, 4°C) for cell harvesting and suspended cells with Pasteur pipettes during the preparation of E. coli competent cells for electrotransformation. As the result, the titer of either BL21 (DE3) or Top10 reached 109 easily, meanwhile at least 1 hr was saved for the whole process.